2020
DOI: 10.4103/ijo.ijo_809_20
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations and outcomes of ocular syphilis in Asian Indian population: Analysis of cases presenting to a tertiary referral center

Abstract: Purpose: To describe disease manifestations and outcomes of ocular syphilis in Asian Indian population. Methods: Retrospective analysis of patients diagnosed with ocular syphilis at a tertiary referral center in India. Demographics, history, extraocular and ocular manifestations, ocular and systemic investigations, treatment and visual acuity outcomes were noted. All patients were diagnosed after necessary laboratory investigations including HIV ELISA (Human immunodefic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
(7 reference statements)
1
6
0
Order By: Relevance
“…Patients must receive repeat therapy if the VDRL titer does not decrease fourfold within one year or if the previously non-reactive VDRL results become reactive again. [10][11][12][13] In this study, the degree of visual impairment before and three months after therapy showed improvement. The same results were also found in a study by Tsuboi et al, where 89% of eyes showed an increase in best corrected visual acuity (BCVA) after 21 months of therapy.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Patients must receive repeat therapy if the VDRL titer does not decrease fourfold within one year or if the previously non-reactive VDRL results become reactive again. [10][11][12][13] In this study, the degree of visual impairment before and three months after therapy showed improvement. The same results were also found in a study by Tsuboi et al, where 89% of eyes showed an increase in best corrected visual acuity (BCVA) after 21 months of therapy.…”
Section: Discussionsupporting
confidence: 52%
“…Tyagi et al His research also showed that 54% of ocular syphilis manifestations were bilateral. 6,13 A total of 14 (93%) of the research subjects were male. These results are in accordance with various studies in other countries, where syphilis sufferers are male, ranging from 56-89%.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of neurosyphilis is with intravenous aqueous penicillin G for 10 to 14 days; in the case of a penicillin allergy, desensitization (recommended), ceftriaxone, doxycycline, or tetracycline are alternatives . The visual outcome after treatment is variable, with syphilis uveitis having the most improvement and optic neuritis having poor visual prognosis …”
Section: Discussionmentioning
confidence: 99%
“…3,4 The visual outcome after treatment is variable, with syphilis uveitis having the most improvement and optic neuritis having poor visual prognosis. 3,5,9 Patient Outcome Fundus autofluorescence did not reveal a classic placoid lesion, but his rapid plasma reagin test and syphilis antibody test results were both positive. HIV testing was negative.…”
Section: Jama Ophthalmology Clinical Challengementioning
confidence: 98%
See 1 more Smart Citation